Does permissive hypoxaemia during extracorporeal membrane oxygenation cause long-term neurological impairment?: A study in patients with H1N1-induced severe respiratory failure. Issue 2 (February 2017) - Holzgraefe, Bernhard; Andersson, Christin; Kalzén, Håkan; von Bahr, Viktor; Mosskin, Mikael; Larsson, Elna-Marie; Palmér, Kenneth; Frenckner, Björn; Larsson, Anders
Abstract : BACKGROUND: The Extracorporeal Life Support Organisation accepts permissive hypoxaemia in adult patients during extracorporeal membrane oxygenation (ECMO). The neurological long-term outcome of this approach has not yet been studied. OBJECTIVES: We investigated the prevalence of brain lesions and cognitive dysfunction in survivors from the Influenza A/H1N1 2009 pandemic treated with permissive hypoxaemia during ECMO for severe acute respiratory distress syndrome (ARDS). Our hypothesis was that this method is reasonable if tissue hypoxia is avoided. DESIGN: Long-term follow-up study after ECMO. SETTING: Karolinska University Hospital, Sweden, from October 2012 to July 2013. PATIENTS: Seven patients treated with ECMO for severe influenza A/H1N1-induced ARDS were studied 3.2 years after treatment. Blood lactate concentrations were used as a surrogate for tissue oxygenation. INTERVENTIONS: Neurocognitive outcome was studied with standardised cognitive tests and MRI of the brain. MAIN OUTCOME MEASURES: Cognitive functioning and hypoxic brain lesions after permissive hypoxaemia during ECMO. The observation period was the first 10 days of ECMO or the entire treatment period if shorter than 10 days. RESULTS: Eleven of 13 patients were still alive 3 years after ECMO. We were able to contact seven of these patients (mean age 31 years), who all agreed to participate in this study. Mean ± SD peripherally measured arterial saturation during the observation period was 79 ± 10%. Full-scale Intelligence Quotient was within one standard deviation or above from the mean of a healthy population in five patients, and was 1.5 SD below the mean in one patient. In one other patient, it could not be determined because of a lack of formal education. Memory functioning was normal in all patients. MRI showed no changes related to cerebral hypoxia. CONCLUSIONS: Permissive hypoxaemia during ECMO might not negatively affect long-term cognitive outcome if adequate organ perfusion is maintained. TRIAL REGISTRATION: at Clinicaltrials.gov NCT01763060